ANALYSIS OF CODE MIXING IN A1 CLASS OF ENGLISH EDUCATION STUDY PROGRAM 2016 - Nurhasanah, Lina (IKIP Siliwangi, 2020)
Code mixing has become a bilingual communication trend that is widely applied by the community in social interactions, especially Indonesian society and students. The method that used in this research is descriptive qualitative. The subjects of this study were English education students who had different ethnic backgrounds and areas of origin. The researcher focused on student utterances that contained by code mixing in the communication. This research was found three types of code mixing used by students namely insertion, alternation, and congruent lexicalization from the English into Indonesia by the students utterances in communication.Keywords:code mixing, kinds of code mixing